Love Letters - Macomber, Debbie (New York : Ballantine Books, 2014)
Three guests at the Rose Harbor Inn are touched by letters that prove love is strong enough to overcome any challenge. For Ellie Reynolds, it's a letter that reconnects her with the father she can't remember, and opens the doors for new love. For Maggie Porter, the reemergence of an old love letter from her husband reminds the couple of what's most important and helps them rekindle an old flame. And for Jo Marie Rose, revisiting a letter from her husband Paul who was killed in battle in Afghanistan.
Keywords: Hotelkeepers -- Fiction; Love-letters -- Fiction; Man-woman relationships -- Fiction; Life change events -- Fiction